Customized pachymetric guided epithelial debridement for corneal collagen cross linking - Jankov Mirco; Coskunseven Efekan; Diakonis Vasilios F; Kymionis George D; Yoo Sonia H; Pallikaris Ioannis G (BMC Ophthalmology, 2009)
Abstract Backround We describe a modified method for deepitheliazation prior to corneal cross linking (CXL). The technique may overcome the current corneal pachymetric limitation parameter (over 400 microns) that is necessary for the safety of the procedure without affecting the overall benefits. Methods In a series of two patients, with inferior topographic steepening and regional thinning (less than 400 microns corresponding to the area of corneal steepening), CXL after customized epithelial removal was performed. Results There were no intra- or postoperative adverse events seen by the nine month follow up examination. Stabilization of the corneal ectasia was observed up to nine months post-costumized pachymetric-guided epithelial removal. Conclusion The technique of customized pachymetric-guided epithelial removal is easy to perform and may overcome the limitations of the preoperative corneal pachymetry expanding the application of the procedure in patients with regional corneal thinning.